(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
E-commerce transaction system core II can disclose product information (such as quality, size, function, and so on) to assist the buyer in understanding the products. And they can advertise their products online so that buyer can now see their products. Social media and other online platforms can now be a place where buyers and sellers meet. E-commerce may provide consumers with a streamlined purchasing experience and assist companies in reaching a larger market, eventually resulting in more sales and business expansion. As a result, the project team created a web-based E-Commerce system that automates transactions; with web-based access to E-Commerce for the submission of relevant criteria as well as verification and payment, orders and deliveries can now be conveniently tracked and processed by the E-Commerce Transaction System Core II. The system will include numerous features requested by the customer that will assist researchers in conveniently managing research documents and other requirements. In this Research, E-commerce transaction system core II will offer the research community a consolidated and efficient platform for managing research data and processes for E- Commerce, contributing to the expansion and development of research capabilities at Bestlink College of the Philippines. by making the research data and method more simple, the E- Commerce can focus more on conducting high-quality research and improving the quality of product and customer services.